Fibonacci retracement pattern recognition for forecasting GBP/USD foreign exchange market - Mohd Fauzi Ramli author (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
Knowledge of how deep the impending the forex market price retracement level would be can assist to forecast the forex market trend. Forecasting demands for past market actions with price movement. The exact technical analysis methods the more accurate forecasting. This study is conducted in order to fulfil these following objectives ; to recognize the pattern using the Elliott wave pattern ; to compare accuracypatterns classification between - Nearest Neighbor (KNN) and Linear Discriminant Analysis (LDA) ; to forecast short term forex market using Fibonacci retracement method.